2020
DOI: 10.1186/s10195-020-00553-9
|View full text |Cite
|
Sign up to set email alerts
|

The healing potential of an acutely repaired ACL: a sequential MRI study

Abstract: Background: Recently, there has been renewed interest in primary anterior cruciate ligament (ACL) repair. The aim of this study is to report early clinical and radiological results of a consecutive series of acute ACL tears treated with arthroscopic primary ACL repair within 14 days from injury. Patients and methods: A consecutive series of patients with acute ACL tears were prospectively included in the study. Based on MRI appearance, ACL tears were classified into five types, and tissue quality was graded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Ferretti et al. 5 demonstrated that appearance of an acutely repaired ACL seems normal or close to normal in all but one case (90%) by 3 months and normal in all cases by 6 months.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ferretti et al. 5 demonstrated that appearance of an acutely repaired ACL seems normal or close to normal in all but one case (90%) by 3 months and normal in all cases by 6 months.…”
Section: Discussionmentioning
confidence: 95%
“… 1 , 2 , 3 With the benefit of modern arthroscopic surgical techniques and devices, there has been a renewed curiosity in primary repair of ACL. 4 , 5 This procedure may be a surgical alternative for those patients presenting with functional impairment after acute proximal ACL injuries with potentially less morbidity, although clinical outcomes for ACL repair using modern techniques is still limited. The ACL is the most important restraint to anterior tibial translation, and recent surgical and biomechanical studies have shown that anterolateral rotational instability (ALRI) is the effect of only a combined lesion of the ACL and secondary restraints, such as anterolateral ligament (ALL) and capsule, Segond fracture, and lateral meniscus posterior root (LMPRT).…”
Section: Introductionmentioning
confidence: 99%
“…Ferretti et al. 11 showed good short-term clinical outcomes after ACL repair in acute injuries and also excellent MRI findings with early recovery of a normal morphology and signal intensity.…”
Section: Discussionmentioning
confidence: 97%
“…With the advent of new surgical techniques, materials, and devices, there has been a renewed interest in primary repair of ACL, with some recent studies on ACL repair showing good-to-excellent results and failure rate ranging from 7% to 15% of cases. 9 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation